IMPLEMENTASI METODOLOGI AGILE-SCRUM DALAM PENGEMBANGAN WEBSITE EDUKASI MANGROVE - Zahrah Hayat Arka Putri; Nayli Amirah Firdaus; Najoan Rizki Pradana; Satrio Agna Gemintang (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the implementation of Agile methodology using the Scrum framework in the development of a Mangrove Education Website. The research applies an applied research approach within the field of software engineering, focusing on the practical application of Scrum in a real system development project. The development process was conducted iteratively through several sprints, involving a cross-functional team consisting of a Project Manager, UI/UX Designer, Front-End Developer, and Back-End Developer. Data were collected qualitatively through observation, documentation of sprint activities, backlog records, sprint reviews, and sprint retrospectives. The findings indicate that the implementation of Scrum, as defined in The Scrum Guide, effectively supports transparency, inspection, and adaptation throughout the development lifecycle. Iterative increments enabled continuous improvement of system features, including educational content modules, planting progress dashboards, and carbon absorption visualization. The study concludes that Agile-Scrum is an effective and adaptive approach for developing dynamic, stakeholder-oriented web-based environmental education systems.